The comparative study of the inhibition potential of four plant powders against the Khapra beetle (Trogoderma granarium) - Sonal Sankhala,; Lekhu Gehlot, (The Bioscan, 2025)
This research work aimed to evaluate the adult inhibition potential of powders of four different plants. The bulb of Allium sativum, leaves of Moringa oleifera, rhizome of Curcuma longa and Zingiber officinalewere used against the test insect Trogoderma granarium infesting groundnut seeds. All fourplant powders were applied at threerates of application, i.e. 0.5%, 1% and 2% in 10 gms of groundnut seeds (w/w). The replicates were made for each concentration. The rhizome powder of C.longa showed a maximum inhibition per cent 60.40% while the powders of A.sativum ,M.oleifera and Z. officinale showed 50.52%, 44.95% and 56.26% of inhibition percent respectively, at 2% concentration. All powders gave effective results in causing adult inhibition in all three concentrations (0.5%, 1% and 2%) as compared to the control. KEYWORDS Groundnuts, Trogoderma, Stored grains, Curcuma, Zingiber, Allium, Moringa,Inhibition, Emergence.